Photoluminescence characterization of Al/Al₂O₃/InP MIS structures passivated by anodic oxidation - Mahdjoub, A.; Bouredoucen, H.; Djelloul, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Metal-insulator-semiconductor (MIS) structures were produced by electron beam heating evaporation of Al₂O₃ on InP. Polyphosphate thin films with the thickness of 100 to 150 A were used to passivate the interface InP/Insulator. Photoluminescence spectra were obtained at low temperatures at the various stages of MIS-InP structure formation. At ambient temperature, photoluminescence topography made it possible to characterize the surface state after each technological stage. The interface degradation under the effect of repeated annealing is insignificant up to the temperatures close to 350 °C. Major radiative defects detected using photoluminescence spectrum with energies ranged from 0.95 to 1.15 eV were attributed to the impurity complexes of phosphorus vacancies, concentration of which is substantially reduced in the presence of
anodic oxide.